2021
DOI: 10.1039/d1cp03792g
|View full text |Cite
|
Sign up to set email alerts
|

The role of excited-state character, structural relaxation, and symmetry breaking in enabling delayed fluorescence activity in push–pull chromophores

Abstract: The electronic structure properties of four related push–pull systems are studied using time-dependent density functional theory in connection with detailed wavefunction analysis protocols.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 98 publications
1
15
0
Order By: Relevance
“…It is worthwhile to mention that accurate predictions on ΔE ST have also been recently proposed within the combination of unrestricted Kohn−Sham and restricted open-shell Kohn− Sham framework, 31 as well as with the optimally tuned rangeseparated hybrid functional. 32 For group II, the TD-wb97xd/6-31G//TD-CAM-B3LYP/6-31G(d) is able to properly describe ΔE ST , with an MAE of ∼0.111 eV.…”
Section: Resultsmentioning
confidence: 98%
“…It is worthwhile to mention that accurate predictions on ΔE ST have also been recently proposed within the combination of unrestricted Kohn−Sham and restricted open-shell Kohn− Sham framework, 31 as well as with the optimally tuned rangeseparated hybrid functional. 32 For group II, the TD-wb97xd/6-31G//TD-CAM-B3LYP/6-31G(d) is able to properly describe ΔE ST , with an MAE of ∼0.111 eV.…”
Section: Resultsmentioning
confidence: 98%
“…† The functionals with an increasing amount of non-local orbital exchange would widen the DE ST values, which is consistent with Paper PCCP the previous investigation. 47 It can be found that the B3LYP functional gave relatively accurate frontier orbital energies, band gaps, excited-state energies and DE ST , and there is no obvious difference between the B3LYP and B3LYP + D3 based data. Hence, B3LYP was employed to calculate the ground-state and excited-state properties.…”
Section: Computational Detailsmentioning
confidence: 83%
“…Note, however, that the formal integration basins defining the fragments A and B have to be defined; libwfa allows to do so via the Mulliken‐ or Löwdin‐style population analyses. The CT numbers allow one to describe the transition in terms of the local and CT contributions; they have been used to assign excited‐state character for, for example, interacting chromophores, 26 push–pull systems, 27,28 and transition‐metal complexes 29 . In practice, the analysis proceeds via a two‐step procedure where libwfa computes the CT numbers with respect to individual atoms and the summation over fragments along with further processing is done by the separate TheoDORE program 24 …”
Section: Functionality and Program Structurementioning
confidence: 99%
“…libwfa enables visualization of various densities and orbitals along with population analyses of the computed densities 23 . An interface to the TheoDORE program 24 enables a fragment‐based analysis 25 that can be used for an automatic excited‐state assignment, for example, for interacting chromophores, 26 push–pull systems, 27,28 and transition‐metal complexes 29 . A complementary perspective is provided by a correlated electron–hole pair and a statistical analysis thereof, 30,31 which was used to highlight dynamic charge‐transfer effects in conjugated polymers, 32 elucidate the diffuseness of Rydberg states, 31 and to describe the nature of core‐excited states 33 .…”
Section: Introductionmentioning
confidence: 99%